PP.08.23: LEFT VENTRICULAR HEMODYNAMIC FUNCTION IS ASSOCIATED WITH ABDOMINAL OBESITY IN PATIENTS WITH ARTERIAL HYPERTENSION. (June 2015) - Krzesinski, P.; Stanczyk, A.; Piotrowicz, K.; Gielerak, G.; Uzieblo-Zyczkowska, B.; Skrobowski, A.
Abstract : Objective: Abdominal obesity is associated with increased cardiovascular risk in hypertensives. The aim of this study was to estimate the relation between abdominal obesity and hemodynamic profile evaluated with the use of echocardiography, applanation tonometry (AT) and impedance cardiography (ICG). Design and method: This study involved 144 patients (mean age: 45.2 years) with untreated AH, recruited to the clinical trial NCT01996085. Abdominal obesity was defined when waist circumference (WC) was equal or higher than 88/102 cm (women/men). The clinical evaluation included i.e.: 1/ echocardiographic assessment (VIVID S6, GE Medical System) of left ventricular (LV) ejection fraction (LVEF), indices of LV diastolic function (E/A - mitral flow early (E) and late (A) phase ratio; e' – mitral septal annulus early diastolic velocity, E/e' ratio) and global longitudinal systolic strain (GLSS, reversed to positive values), 2/ AT (SphygmoCor® system): central pulse pressure (CPP) and augmentation index (AI) and 3/ ICG (Niccomo™ device): systemic vascular resistance index (SVRI); cardiac index (CI), acceleration index (ACI); velocity index (VI), thoracic fluid content (TFC) and total artery compliance (TAC). The comparison between obese and not obese subjects was supplemented with the assessment of correlation between WC and the above mentioned hemodynamic variables. Results: Obese hypertensives characterized with: worse diastolic function (e': 9.08 ± 2.69 vs 10.39 ± 2.34 cm/s. p = 0.003; E/e': 7.54 ± 1.81 vs 6.74 ± 1.40. p = 0.007; E/A: 1.02 ± 0.34 vs 1.15 ± 0.33; p = 0.008) and lower echocardiographic (GLSS: 17.2 ± 2.5 vs 19.0 ± 2.8%, p = 0.0002) and impedance indices of LV performance (VI: 44.8 ± 12.4 vs 51.6 ± 14.2 1000*Ohm/s; p = 0.006; ACI: 66.7 ± 27.8 vs 79.1 ± 31.2 100*Ohm/s2; p = 0.003). LV diastolic function was impaired in 35.4% obese subjects compared to 10.8% of the non-obese (p = 0.0006). No relevant differences in gender, age, blood pressure, heart rate, LVEF, E/A, SVRI, TFC, TAC, CPP and AI were identified. Correlation analysis revealed significant associations between WC and e' (−0.22; p = 0.010); E/A (−0.26; p = 002); VI (−0.47; p < 0.000001) and ACI (−0.41; p < 0.000001). Conclusions: Obese patients characterized with slightly impaired LV diastolic and systolic function and no significant alterations in afterload and fluid balance. In young and middle aged obese hypertensives asymptomatic depression of cardiac function can be the earliest clinical feature of impaired ventricular-vascular interactions.